Work conditions and accidents in three industries. - Saari, Jorma; Lahtela, Jari (Scandinavian Journal of Work, Environment & Health, 1981)
Four studies conducted in the light metal, electrotechnical and printing industries are described. The purpose was to determine the applicability of the systems approach to occupational accidents. The data consisted of 291 accidents and 701 controls. The stable characteristics of the workers or the environments were not good predictors of accidents. The clearest differences between the accidents and the controls involved the worker`s situational experience, the frequency of task occurrence, the familiarity of the tasks, and the mobility of dangers. The complexity of the information exchange between man and his environment, as well as the perceptibility of environmental dangers, contributed to the occurrence of accidents.
Keywords: accident; danger; experience; industry; systems approach; task; work condition